Indicadores de estresse ambiental em populações de Leptodactylus macrosternum (Leptodactylidae) e Scinax x-signatus (Hylidae) em ambientes agrícolas no semi-árido brasileiro - Gondim, Patrícia de Menezes (2022)
The agriculture has been cited as one of factors responsible for the current decline in amphibian populations due to the expansion of cultivated areas and pastures, irrigation practices and the use of fertilizers and pesticides. In order to evidence interferences of agricultural areas in the Brazilian semi-arid region in the organs of two species of anurans, we used different types of indicators, such as morphological and histological. In the manuscript I, we compared fluctuating asymmetry and organosomatic indices in populations of Leptodactylus macrosternum and Scinax x-signatus between areas with agricultural and non-agricultural activities which are located in the Lower Jaguaribe River, an important microregion for agribusiness in the state of Ceará. In the manuscript II, we compared morphohistology in populations of Leptodactylus macrosternum between these same areas. The fluctuating asymmetry in the femur length of Leptodactylus macrosternum and in the calcaneus-phalange lenght of Scinax x-signatus did not show significant diferences while the hepatosomatic, adiposomatic and gonadosomatic indices of Leptodactylus macrosternum varied widely between áreas. In this species, we also registered a decrease in the frequency of spermatogenic cells in the differentiation stage (spermatids II and sperm) and an increase in the frequency of stasis in areas with agricultural activities. Mild chronic inflammatory infiltrates, punctual tubular necrosis, spermatocyte degeneration and focal Leydig cell hyperplasia were also more frequent in areas with agricultural activities. The set of results may indicate how agricultural activities affect the stages in the life history of species and populations (growth, survival and reproduction). Therefore, future studies will focus on possible histopathological findings in other endocrine organs and contamination by pesticides and heavy metals in endocrine and lymphoid organs of the same L. macrosternum individuals collected here.